A study on damage to mechanical seat cushion made from different materials of extension frame - Won Kim, Jae; Ung Cho, Jae; Ki Cho, Chan; Oh Kim, Jin (International Journal of Engineering and Technology, 2018)
Background/Objectives: : Automotive seat is a very important component to prevent accidents by reducing passengerâ€™s tiredness, thus, this study worked on analyzing damage with different materials of extension frames of mechanical seat cushions.Methods/Statistical analysis: In this study, we performed an experiment on cushion extension frames by splitting it into two parts. We studied about the damage prediction of slave body for each material property of ABS, PP, PLA, and PA6.6. For analyzing the condition, we assigned the side part of the master body for fixed support, and we progressed on analysis by applying with 690N on the entire part of the slave body.Findings: This research worked on the study of damage to different materials of extension frames of seat cushions. After confirming the stress equivalence of the entire model for each material, PP showed the highest equivalent stress of 180.88MPa, and ABS showed the lowest equivalent stress of 151.73MPa. Overall, we could see that in the order of ABS, PA6.6, PLA, PP have a higher tendency to be broken. In addition, when confirming equivalent stress of master body depending on materials of slave body, PA6.6 showed the highest equivalent stress of 166.3MPa, and ABS showed the lowest equivalent stress of 124.06MPa. Overall, we could see that in the order of ABS, PP, PLA and PP6.6 have a higher tendency to be broken. In comparing shear stress on the gear part, which has the highest tendency to be broken in among the entire model, depending on the material of the slave body, PLA showed the greatest shear stress of 88.945MPa, and ABS showed the lowest shear stress of 69.766MPa.Improvements/Applications: This study worked for the improvements and applications of cushion extension frames as the securement of material by investigating these factors.Â Â